Buckling, build orientation, and scaling effects in 3D printed lattices. (December 2018) - Mueller, Jochen; Shea, Kristina
Abstract : Graphical abstract: Abstract: Cellular lightweight structures offer superior mechanical properties when compared to their bulk counterparts. Fabricating them, however, remains a challenge as even the most advanced processes exhibit considerable limitations. Material jetting, also referred to as (inkjet) 3D printing, offers multi-material capability, which, in combination with soluble support material, makes it a capable alternative to conventional processes. However, while the process is well investigated on a macro scale, these findings do not apply to small feature sizes. Here, we study the impact of buckling, build-orientation, and scaling on the mechanical properties at scales that approach the printers' limits. Strong interaction effects and large discrepancies from macro scale parts are found. Specifically, the findings show that complete stress–strain curves can be accurately predicted when these effects are considered, whereas conventional material models tend to overestimate the mechanical properties of bend- and stretch-dominated lattices by up to an order of magnitude. This is particularly important for safety-critical and highly efficient parts. Further, the findings might help to establish the material jetting process in the field of cellular structures, which has to date been dominated by single material processes.